Organizational and structural approaches on administrative simplification: The case of Kosovo - Ruzhdi Halili; Simona Kukovič (Administrative Sciences, 2022)
Administrative simplification is a particular approach that is considered a key aspect to ensure the quality of regulations and legislation. The appropriate organizational and structural approach to managing, coordinating, and monitoring administrative simplification is an important factor. The institutional framework for managing and coordinating administrative simplification initiatives has been the subject of discussions in the Government of Kosovo for several years. The objective of this paper is therefore to analyze the institutional set up in the central administration, as well as gaps and challenges, and their implications for the implementation of such reforms in Kosovo. It also presents the context of the reforms implemented by the Kosovo state administration to simplify administration and reduce administrative burdens. Particular attention is paid to the importance, status of implementation, and administration of the Law on General Administrative Procedures. Several recommendations and options have been made based on the findings of this study, the authors' first-hand experience, and best comparative international practice.
Keywords: 350; administrative simplification; good governance; Kosovo; quality of regulations; reforms